Analisis Kapasitas Produksi dan Pemenuhan Permintaan dengan Model Sistem Dinamis pada Industri Semen - Karima, Halim Qista; Saputra, Mas Aji; Romadlon, Fauzan (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2022)
Planning production capacity to meet demand is a challenge for companies. Inventory and fulfillment rate problems become an issue in every planning process. The company aims to minimize inventory and maximize the level of demand fulfillment. Small production activities will minimize total inventory but reduce the level of demand fulfillment, and vice versa. The system dynamic modeling was chosen to model the condition of the production system in determining the medium-term strategy. Dynamic systems are very appropriate for simulating policies and evaluating the conditions of production systems. System dynamic modeling using Vensim software. Based on the model results, it is found that the installed capacity production will be able to meet the demand for the next six years. To meet demand in the next 8 years, the company can increase its grinding machine pro